2007
DOI: 10.1037/0022-006x.75.6.901
|View full text |Cite
|
Sign up to set email alerts
|

A multisite investigation of binge eating behaviors in children and adolescents.

Abstract: The phenomenology of childhood and adolescent loss of control (LOC) eating is unknown. The authors interviewed 445 youths to assess aspects of aberrant eating. LOC was associated with eating NIH-PA Author ManuscriptNIH-PA Author Manuscript NIH-PA Author Manuscript forbidden food before the episode; eating when not hungry; eating alone; and experiencing secrecy, negative emotions, and a sense of "numbing" while eating (ps < .01). Hierarchical cluster analysis revealed a subgroup, most of whom reported LOC eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
195
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(214 citation statements)
references
References 99 publications
(149 reference statements)
16
195
1
2
Order By: Relevance
“…For example, binge eating may provide a distraction from external stressors (Heatherton & Baumeister, 1991) or enable a "trade-off," whereby the aversive emotions preceding binge eating (e.g., anger) are replaced by less aversive emotions subsequent to binge eating (e.g., guilt; Kenardy, Arnow, & Agras, 1996). Indeed, preliminary evidence suggests that youth with LOC eating problems are more likely than those without eating problems to endorse emotional eating in general (Goossens, Braet, & Decaluwe, 2007;, and to report that LOC eating episodes occurred in response to a negative emotion (Tanofsky-Kraff, Goossens, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, binge eating may provide a distraction from external stressors (Heatherton & Baumeister, 1991) or enable a "trade-off," whereby the aversive emotions preceding binge eating (e.g., anger) are replaced by less aversive emotions subsequent to binge eating (e.g., guilt; Kenardy, Arnow, & Agras, 1996). Indeed, preliminary evidence suggests that youth with LOC eating problems are more likely than those without eating problems to endorse emotional eating in general (Goossens, Braet, & Decaluwe, 2007;, and to report that LOC eating episodes occurred in response to a negative emotion (Tanofsky-Kraff, Goossens, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas by adulthood, most individuals with BN and BED report an extensive dieting history (e.g., de Zwaan et al, 1994;Kurth, Krahn, Nairn, & Drewnowski, 1995), some (Decaluwe & Braet, 2005;Field et al, 2003;Tanofsky-Kraff et al, 2004) but not all (Claus, Braet, & Decaluwe, 2006;Decaluwe, Braet, & Fairburn, 2003;Glasofer et al, 2007) cross-sectional studies in children support an association between dieting and binge eating. In one study, most children recalled the onset of LOC eating prior to their first attempt at dieting (Tanofsky-Kraff, Faden, Yanovski, Wilfley, & Yanovski, 2005), and another study found that only a minority endorsed having eaten a forbidden food and/or restricting their food intake prior to an episode of LOC eating (Tanofsky-Kraff, Goossens, et al, 2007). Similarly inconsistent findings regarding the role of dieting in the etiology of BED are reported (e.g., Howard & Porzelius, 1999;Spurrell, Wifley, Tanofsky, & Brownell, 1997), and are in contrast to BN, in which dieting typically precedes and helps maintain the disorder (e.g., Pederson Mussell et al, 1997;Fairburn, Stice, Cooper, Doll, Norman, & O'Connor, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Also, children with symptoms of BED engage in eating in response to negative affect. [4][5][6] Yet, it is unclear whether binge eating in children is associated with deficits in emotion regulation and which emotion regulation strategies are problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Eine weitere relevante Frage ist, ob diese Maße von negativem Affekt beeinflusst werden. Denn Kinder mit Essanfällen berichten zwar retrospektiv, dass negativer Affekt ihren Essanfällen vorausgeht Eddy et al, 2007;Tanofsky-Kraff, Goossens et al, 2007;Tanofsky-Kraff, Theim et al, 2007), ein solcher Zusammenhang konnte jedoch sowohl im Labor (Hilbert et al, 2010) als auch im natürlichen Lebensalltag (Hilbert, Rief, Tuschen-Caffier, de Zwaan, Czaja, 2009) nicht eindeutig belegt werden, was die Gül-tigkeit von Störungsmodellen, die eine antezedente negative Stimmung als einen der wichtigsten Aufrechterhaltungsfaktoren für Essanfälle konzeptualisieren (Castonguay, Eldredge, Agras, 1995;Fairburn, Cooper, Shafran, 2003;Goldschmidt, Aspen, Sinton, Tanofsky-Kraff, Wilfley, 2008;Waters, Hill, Waller, 2001) (Glasofer et al, 2007;Hilbert u. Czaja, 2007;Hilbert et al, 2010).…”
Section: Hintergrundunclassified